CURRENT SITUATION AND PROSPECTS OF DEVELOPMENT OF VEGETABLES, MELONS AND PUMPKIN BREEDING AND SEED PRODUCTION - V.F. Pivovarov; O.N. Pyshnaya; L.K. Gurkina (Овощи России, 2011)
The main achievements of vegetable breeding research in different institutions of Russian Federation and the priorities and prospects were highlighted in the article.